Impact of hemoadsorption with CytoSorb® on meropenem and piperacillin exposure in critically ill patients in a post-CKRT setup: a single-center, retrospective data analysis - Golschan Asgarpur; Franz Weber; Peggy Kiessling; Nilufar Akbari; Fabian Stroben; Bernadette Kleikamp; Charlotte Kloft; Sascha Treskatsch; Stefan Angermair (Intensive Care Medicine Experimental, 2025)
Abstract Purpose CytoSorb® (CS) adsorbent is a hemoadsorption filter for extracorporeal blood purification often integrated into continuous kidney replacement therapy (CKRT). It is primarily used in critically ill patients with sepsis and related conditions, including cytokine storms and systemic inflammatory responses. Up to now, there is no evidence nor recommendation for the use of CS filters in sepsis (22). There is limited clinical data on the effect of CS on the plasma concentrations of beta-lactams. We aimed to evaluate the statistical and clinical impact of CS in a post-filter CKRT-CS setting on the plasma concentrations of the antibiotics meropenem and piperacillin in critically ill patients. Methods Patients admitted to the intensive care unit (ICU) who received a prolonged infusion of piperacillin or meropenem with CS-combined CKRT were included in this retrospective analysis. TDM (therapeutic drug monitoring) plasma blood samples were collected at three different points. The differences in antibiotic concentrations between Pre, Intra, and Post were statistically compared to evaluate the total and isolated contributions of CKRT and CS to antibiotic removal. CS, CKRT and combined clearance (CL) values were calculated. The hypothesis was that the CS filter would have no clinically relevant impact on antibiotic levels. Results 207 TDM samples were taken from 24 critically ill patients requiring beta-lactam antibiotics. Among these, 129 were meropenem samples, and 78 were piperacillin samples. A decrease in both antibiotic levels was observed between Pre and Intra, and Pre and Post, and the median relative difference between was >15% (meropenem: Pre–Intra 34.8%, Pre–Post 35.8%; piperacillin: Pre–Intra 41.1%, Pre–Post 34.7%), indicating a statistically and clinically significant effect of CKRT on both antibiotic exposures. No significant difference was observed between Intra and Post indicating no clinically relevant drug removal via the CS filter. Changes in CL attributed to CS were minimal, with combined CL differing by ≤8.60% compared to CKRT clearance. Conclusion The application of CS does not appear to significantly affect plasma concentrations of meropenem and piperacillin in critically ill patients.